Evaluating the role of FAMIly history of cancer and diagnosis of multiple neoplasms in cancer patients receiving PD-1/PD-L1 checkpoint inhibitors: the multicenter FAMI-L1 study. (1st January 2020) - Cortellini, Alessio; Buti, Sebastiano; Bersanelli, Melissa; Giusti, Raffaele; Perrone, Fabiana; Di Marino, Pietro; Tinari, Nicola; De Tursi, Michele; Grassadonia, Antonino; Cannita, Katia; Tessitore, Alessandra; Zoratto, Federica; et al.
ABSTRACT: Background : We investigate the role of family history of cancer (FHC) and diagnosis of metachronous and/or synchronous multiple neoplasms (MN), during anti-PD-1/PD-L1 immunotherapy. Design : This was a multicenter retrospective study of advanced cancer patients treated with anti-PD-1/PD-L1 immunotherapy. FHC was collected in lineal and collateral lines, and patients were categorized as follows: FHC-high (in case of cancer diagnoses in both the lineal and collateral family lines), FHC-low (in case of cancer diagnoses in only one family line), and FHC-negative. Patients were also categorized according to the diagnosis of MN as follows: MN-high (>2 malignancies), MN-low (two malignancies), and MN-negative. Objective response rate (ORR), progression-free survival (PFS), overall survival (OS), and incidence of immune-related adverse events (irAEs) of any grade were evaluated. Results : 822 consecutive patients were evaluated. 458 patients (55.7%) were FHC-negative, 289 (35.2%) were FHC-low, and 75 (9.1%) FHC-high, respectively. 29 (3.5%) had a diagnosis of synchronous MN and 94 (11.4%) of metachronous MN. 108 (13.2%) and 15 (1.8%) patients were MN-low and MN-high, respectively. The median follow-up was 15.6 months. No significant differences were found regarding ORR among subgroups. FHC-high patients had a significantly longer PFS (hazard ratio [HR] = 0.69 [95% CI: 0.48–0.97], p = .0379) and OS (HR = 0.61 [95% CI: 0.39–0.93], p = .0210), when compared to FHC-negative patients. FHC-high was confirmed as an independent predictor for PFS and OS at multivariate analysis. No significant differences were found according to MN categories. FHC-high patients had a significantly higher incidence of irAEs of any grade, compared to FHC-negative patients ( p = .0012). Conclusions : FHC-high patients seem to benefit more than FHC-negative patients from anti-PD-1/PD-L1 checkpoint inhibitors.